Brain-targeted drug delivery assisted by physical techniques and its potential applications in traditional Chinese medicine - Yunbo Sun; Lina Du; Meiyan Yang; Qi Li; Xueli Jia; Qian Li; Lin Zhu; Yuanyuan Zhang; Yijing Liu; Shuchen Liu (Journal of Traditional Chinese Medical Sciences, 2021)
The blood–brain barrier (BBB) constitutes a major obstacle to effective delivery of drugs to the brain. Recent technological advances have led to improvements in brain-targeted drug delivery. In this review, we summarize existing technologies for efficient drug delivery across the BBB. We discuss the mechanisms of current BBB-based drug delivery strategies and introduce prospects for application in brain-targeted delivery of traditional Chinese medicine. We highlight the use of physical techniques for brain-targeted drug delivery, including electroporation, ultrasound, magnetophoresis, microneedles, microwaves, and laser. The characteristics of these techniques and relevant studies employing these approaches are discussed. In general, microneedles, lasers, ultrasound, electroporation, magnetophoresis, and microwaves are effective for drug delivery across the BBB. Notably, the synergistic effects of multiple approaches are superior to the additive effects of each technique in isolation. Our review provides guidance for the practical application of brain-targeted drug delivery techniques in an efficient and safe manner.